Social Dominance - Ludger Schuknecht; Holger Zemanek (Center for Economic Studies and ifo Institute (CESifo), 2018)
Based on the observation of an unabated trend towards higher social spending ratios in advanced countries, the study analyzes the risk of “social dominance”, where social expenditures dominate fiscal policy, and undermine growth and fiscal sustainability. We scrutinize this risk by analyzing drivers of social expenditures and their interaction with other fiscal variables. Results show, that social expenditure expansion is largely ageing driven, it crowds out other primary expenditures and there is evidence of unsustainability. These findings and the accelerating trend of population ageing and particularly high political costs to reforming social expenditure suggest significant and rising risks of “social dominance".
Keywords: E62; H30; H55; 330; fiscal policy; social expenditures; political economy; crowding out; fiscal sustainability